The role of motivation in the conceptual model of motor development in childhood. (July 2022) - Menescardi, Cristina; De Meester, An; Morbée, Sofie; Haerens, Leen; Estevan, Isaac
Abstract: The aim of this study was twofold: first, to investigate whether perceived motor competence (PMC) mediates the relation between actual motor competence (AMC) and physical activity (PA) according to the conceptual model of motor development, and second to examine the role of different motivational regulations (i.e., intrinsic, identified, introjected, and external regulation) in the relationship between PMC and PA. A sample of 504 Spanish students (46.2% girls, 8–12 years old) voluntarily participated in this study. In relation to the first aim, structural equation modeling revealed that PMC indeed mediates the association between AMC and PA. In relation to the second aim, positive associations between AMC and PMC (β = 0.32, p < .001), which in turn was positively related to intrinsic and identified regulations (β = 0.46 and β = 0.43 respectively, p < .001), were found. The model showed direct paths from intrinsic and introjected regulation to PA (β = 0.27 and β = 0.22, p < .05) and indirect paths from PMC through intrinsic motivation to PA (β = 0.13, p < .05). This study confirms that intrinsic motivation mediates the association between PMC and PA. Strategies targeting to build and develop children's AMC and PMC, and fostering children's intrinsic motivation should be targeted to promote children's PA engagement and motor development. Highlights: The mediation role of children's perceived motor competence in the relation between their actual motor competence and physical activity is evidenced. The association between children's perceived motor competence and physical activity is mediated by intrinsic motivation. The examination of the role of the motivational regulations in between the children's perceived motor competence-physical activity relation into the conceptual model of motor development requires further research. In addition to developing children's actual and perceived motor competence, it is important to foster their intrinsic motivation to promote physical activity engagement.